2015
DOI: 10.1364/oe.23.002846
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tuneable lateral leakage loss in liquid crystal clad shallow-etched silicon waveguides

Abstract: Abstract:We demonstrate electrical tuning of the lateral leakage loss of TM-like modes in nematic liquid crystal (LC) clad shallow-etched Siliconon-Insulator (SOI) waveguides. The refractive index of the LC layer can be modulated by applying a voltage over it. This results in a modulation of the effective index of the SOI waveguide modes. Since the leakage loss is linked to these effective indices, tunable leakage loss of the waveguides is achieved. We switch the wavelength at which the minimum in leakage loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In [19], the existence of strong TE radiation as well as suppression of this radiation at the 'magic' widths were also demonstrated by directly observed the radiating TE field on both sides of the ridge. Further investigations have demonstrated that the lateral leakage loss can be electrically tuned when using liquid crystal (LC) as the cladding materials [20], [21].…”
Section: Experimental Observation Of Lateral Leakage In Soi Ridge mentioning
confidence: 99%
“…In [19], the existence of strong TE radiation as well as suppression of this radiation at the 'magic' widths were also demonstrated by directly observed the radiating TE field on both sides of the ridge. Further investigations have demonstrated that the lateral leakage loss can be electrically tuned when using liquid crystal (LC) as the cladding materials [20], [21].…”
Section: Experimental Observation Of Lateral Leakage In Soi Ridge mentioning
confidence: 99%
“…The quasi‐TE mode of such a ridge propagates with low loss and is commonly used in silicon photonics for optical transport . Our team discovered that the quasi‐TM mode can radiate strongly and equally to the TE slab mode on either side (as illustrated in Figure b), an effect called lateral leakage . The generated TE slab mode propagates at a particular angle to the waveguide axis given by θ=cos1ntmntewhere ntm and nte are the effective index of the quasi‐TM guided mode and TE slab mode in the claddings, respectively.…”
Section: Lateral Leakage Of Tm Mode In a Ridge: Leakage Of The Bound mentioning
confidence: 99%
“…It can be seen from Figure e that the angular bandwidth of the reflection depends strongly on the ridge width. When the ridge width approaches the “magic” width at which the lateral leakage loss of the guided quasi‐TM mode is zero, the angular bandwidth of the reflection also approaches zero. This phenomenon indicates the presence of bound states in the continuum when the ridge at the “magic” width is excited with a TE beam at an angle resulting in phase matching between the exited TE beam and quasi‐TM guided mode in the ridge.…”
Section: Te Slab Beam Incident On a Ridge: Excitation Of The Bound Stmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the field outside the core, i.e., the evanescent field, allowing for easy modification of overall guiding properties. Tuning the evanescent field is possible by changing the effective refractive index of the cladding, by means of an active electrooptical material such as liquid crystal (LC) [1]. On the other hand, the fabrication process determines the dimensions and shape of the waveguide.…”
mentioning
confidence: 99%